IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE NHT PADA PEMBELAJARAN TEMATIK SISWA KELAS III DI SD NEGERI 63 PALEMBANG - Subakti, Tegar; Idris, Muhamad; Budi Irawan, David (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of the Numbered Heads Together (NHT) cooperative learning model in thematic learning for third-grade students at SD Negeri 63 Palembang, which is motivated by the low student activeness due to the dominance of conventional teaching methods. Using a qualitative method with a case study approach, data were collected through observation, interviews, and documentation, then analyzed through data reduction, data presentation, and conclusion drawing with data validity ensured through source and technique triangulation. The results showed that the implementation of the NHT model was carried out through three stages: planning (developing lesson plans based on the 2013 Curriculum), implementation (opening, core activities including group formation, numbering, discussion/heads together, random number calling, and closing), and evaluation (written tests and process assessment). The application of the NHT model proved to increase student activeness in discussions, group cooperation, and confidence in expressing opinions, as well as facilitating understanding of the material on the symbols of Pancasila principles in the Garuda Pancasila emblem by creating an interactive and student-centered learning atmosphere, although there were obstacles such as less active students and time constraints that could be overcome through guidance and better time management. In conclusion, the implementation of the NHT cooperative learning model has a positive impact on student activeness and understanding and has been carried out according to the planned stages.